Strongly Summable Vector-Valued Sequence Spaces Defined by 2-modular - Nurnugroho, Burhanudin Arif; Prasetyo, Puguh Wahyu (CAUCHY, 2021)
Summability is an important concept in sequence spaces. One summability concept is strongly Cesaro summable. In this paper, we study a subset of the set of all vector-valued sequence in 2-modular space. Some facts that we investigated in this paper include linearity, the existence of modular and completeness with respect to these modular.